2020
DOI: 10.3847/1538-4357/abbc1c
|View full text |Cite
|
Sign up to set email alerts
|

The Sloan Digital Sky Survey Reverberation Mapping Project: Estimating Masses of Black Holes in Quasars with Single-epoch Spectroscopy

Abstract: It is well known that reverberation mapping of active galactic nuclei (AGNs) reveals a relationship between AGN luminosity and the size of the broad-line region, and that use of this relationship, combined with the Doppler width of the broad emission line, enables an estimate of the mass of the black hole at the center of the active nucleus based on a single spectrum. An unresolved key issue is the choice of parameter used to characterize the line width, either FWHM or line dispersion s line (the square root o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 196 publications
7
77
0
Order By: Relevance
“…Several studies show that many AGNs, including some of the highest accretion rate objects, fall below the usual R BLR À L AGN relation (see Figure 9; Du et al, 2015Du et al, , 2016Du et al, , 2018Grier et al, 2017b;Fonseca Alvarez et al, 2020). While the reason is not currently understood, some ascribe it to physical changes arising from high accretion rates (e.g., Dalla Bontà et al, 2020) while others have suggested that is related to differences in the shape of the ionizing continuum (e.g., Fonseca . Nevertheless, what is clear is that local Seyferts may not, in fact, be appropriate models for high-z quasars, and estimating M BH for large numbers of AGNs that span the full range of observed properties is more complicated than previously assumed.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Several studies show that many AGNs, including some of the highest accretion rate objects, fall below the usual R BLR À L AGN relation (see Figure 9; Du et al, 2015Du et al, , 2016Du et al, , 2018Grier et al, 2017b;Fonseca Alvarez et al, 2020). While the reason is not currently understood, some ascribe it to physical changes arising from high accretion rates (e.g., Dalla Bontà et al, 2020) while others have suggested that is related to differences in the shape of the ionizing continuum (e.g., Fonseca . Nevertheless, what is clear is that local Seyferts may not, in fact, be appropriate models for high-z quasars, and estimating M BH for large numbers of AGNs that span the full range of observed properties is more complicated than previously assumed.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…An acceptable compromise is the use of single-epoch spectra with proper calibration relationships. Among the different options, the use of the line dispersion σ line yields better results than the FWHM one, because the σ line is less affected by the inclination and the accretion rate [43,48,49]. One would expect that for a given mathematical profile the two quantities are related, but observations indicate something different and I refer to the excellent works by [43,48,49] for more detailed analyses.…”
Section: The Mass Of the Central Black Hole Of A Jetted Agnmentioning
confidence: 99%
“…Both the resolutioncorrected FWHM and σ line measured from the mean and rms spectra of Hβ are used as ∆V. A value of f = 4.47 (1.12) is adopted when σ line (FWHM) is considered as ∆V (Woo et al 2015), however, note that FWHM is a non-linear function of σ line (e.g., Peterson 2014;Bonta et al 2020). Finally, four different black hole masses are determined based on the four different choices of line widths (see Table 4).…”
Section: Line Width and Black Hole Massmentioning
confidence: 99%